Modelo e plano de negócios para uma empresa de consultoria em engenharia de produção - (:unkn) unknown (Universidade Federal do Pampa, 2016)
Nowadays, Brazil is considered a very enterprising country, this fact increasingly shows the need for a well-prepared planning by the entrepreneur, to ensure that companies stay in the market. To accomplish such planning, there are two tools of great value, one of them is the Canvas tool that facilitates the interpretation of one business model, the other is the business plan that allows to evaluate the economic and financial feasibility of the enterprise. This work intends to determine if it is economically feasible to open a consulting company in Production Engineering in the city of Bagé. The treatment that will be used will investigate information about the companies located in Bagé, such as number of companies and the size in which they fit, both to verify the opportunity to open a consultancy and to identify the competition. In addition, it is intended to specify the knowledge of a production engineer to open new business. In the results, a business model proposal is presented through the elaboration of the Canvas illustrating how the company intends to operate, a business plan that shows the economic feasibility of the enterprise since it is carried out in partnership with the Federal University of Pampa - UNIPAMPA through Incubation of the consulting company. A table containing all the items to develop a business plan was related to the contents covered in the course of Production Engineering and, together with the areas of knowledge of the ABEPRO matrix, expose the knowledge of an egress from the Production Engineering course to Plan a business. At the end of the study, the complexity of developing a business plan was identified, especially in the market analysis. The importance of the university to assist in the development of new ventures was also observed. Regarding the Engineer's abilities to prepare a business plan, the contents learned in the course cover practically all the items of development of a business plan.
Keywords: Engenharia; Engenharia de produção; Modelo de negócios; Plano de negócios; ABEPRO; Consultoria; Canvas; CNPQ::ENGENHARIAS